Facebook Live: A Mixed-Methods Approach to Explore Individual Live Streaming Practices and Motivations on Facebook. Issue 6 (2nd January 2020) - Skjuve, Marita; Brandtzaeg, Petter Bae
Abstract: : In April 2016, Facebook launched Facebook Live. Yet, how and why people stream on Facebook Live is poorly understood. Guided by the uses and gratifications theory, we analyzed public, individual live stream videos on Facebook Live ( N = 1118) from the USA, Europe and Asia and applied a questionnaire to Facebook Live users ( N = 246) in the USA. We found 14 different live streaming practices, the two most common of which were chatting with random people (seen in 48% of the videos) and demonstrations of skills (seen in 10% of the videos). We also identified live streaming sessions that were problematic and challenged Facebook guidelines. From the questionnaire, we revealed that the most important motivations are (i) socializing with family and friends (reported by 38%), (ii) sharing opinions and experiences (reported by 16%) and (iii) entertainment/fun (reported by 15%). Our findings offer insight into the various personal incentives that drive people to stream on Facebook Live and thus contribute to an understanding of the social implications of a new mode of mediated interaction. RESEARCH HIGHLIGHTS: Our findings contribute novel insights into how social media usage among individual streamers is moving towards more immediate forms of interaction in a live streaming environment. Some streaming practices challenge both the Facebook community guidelines and users' privacy. The basic motivations for streaming on Facebook Live are consistent with previous research on the uses and gratifications relating to Facebook in general. However, Facebook Live streaming practices differ with respect to how user-generated content is presented and experienced. Live streaming gives users a greater sense of presence than more traditional social media; however, Facebook Live is used by relatively few and might not represent a major shift in how we communicate.